Characteristics and independent predictors of self‐disclosure among male patients undergoing in vitro fertilization: A cross‐sectional study. - Tang, Shi; Wang, Min; Bao, Yi‐Min; Hu, Su‐Wen; Kong, Xiang‐Lin; Chen, Dan (Perspectives in Psychiatric Care, 2022)
Purpose: To investigate the levels of self‐disclosure in men undergoing in vitro fertilization and analyze the effects of communication and personality on self‐disclosure. Design and Methods: This cross‐sectional study included 210 men undergoing in vitro fertilization. Self‐disclosure was measured using the Chinese Distress Disclosure Index Scale. Findings: Participants with high self‐disclosure exhibited lower neuroticism, higher extraversion, better partner communication, higher educational levels, and were likely to have a child; these factors were independent predictors of self‐disclosure. Practice Implications: These findings highlight the factors influencing self‐disclosure and can aid in developing guidance programs for infertile men.